2018
DOI: 10.1002/adsc.201801028
|View full text |Cite
|
Sign up to set email alerts
|

[4+1] Cycloaddition of Enaminothiones and Aldehyde N‐Tosylhydrazones Toward 3‐Aminothiophenes

Abstract: An efficient protocol toward trisubstituted 3-aminothiophenes has been developed through a [4 + 1] cycloaddition of enaminothiones and aldehyde N-tosylhydrazones under transition-metal-free conditions. 3-Aminothiophene derivatives as well as their chiral analogs were obtained in good to excellent yields. Direct interaction of the enaminothiones with the diazo compounds of a-carbonyl or ester group-functionalized aldehydes also efficiently afforded the same type of 3-aminothiophenes. The diversity of the synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…We recently found that alkylthio‐substituted enaminones and enaminothiones, that is, α‐oxo (thioxo) ketene N,S‐acetals, could undergo carbene insertion reactions to establish O‐ and S‐heterocycles under copper(II) catalysis or metal‐free conditions (Scheme a), and cycloketone oxime esters were also used as the C1 building blocks to react with enaminothiones in the presence of a copper(I) catalyst to give thiophene derivatives (Scheme b) . Thus, we envisioned that sulfur ylides might also act as the suitable C1 building blocks to react with alkylthio‐substituted enaminones and enaminothiones to execute [4+1] annulation to afford multisubstituted furan and thiophene derivatives (Scheme c).…”
Section: Figurementioning
confidence: 99%
“…We recently found that alkylthio‐substituted enaminones and enaminothiones, that is, α‐oxo (thioxo) ketene N,S‐acetals, could undergo carbene insertion reactions to establish O‐ and S‐heterocycles under copper(II) catalysis or metal‐free conditions (Scheme a), and cycloketone oxime esters were also used as the C1 building blocks to react with enaminothiones in the presence of a copper(I) catalyst to give thiophene derivatives (Scheme b) . Thus, we envisioned that sulfur ylides might also act as the suitable C1 building blocks to react with alkylthio‐substituted enaminones and enaminothiones to execute [4+1] annulation to afford multisubstituted furan and thiophene derivatives (Scheme c).…”
Section: Figurementioning
confidence: 99%
“…In 2018, Yu and co-workers studied a formal [4+1]-cycloaddition reaction between diazo compounds and enaminothiones. [46] Diazo compounds were generated mostly in onepot fashion from the corresponding tosylhydrazones and tBuOLi under Bamford-Stevens conditions.…”
Section: Carbene Reactivitymentioning
confidence: 99%
“…[17] However, the number of direct methods for the synthesis of the 3-aminothiophene nucleus, as an alternative of thiophene functionalization, is very limited. [18][19][20][21][22] The main strategy reported in the literature uses a Thorpe -Ziegler type cyclization, but this method possesses some limitations, as the C(2) position of the thiophene is restricted to electron withdrawing groups such as ester or nitrile. [23 -30] Based on our previous work on the synthesis of 3aminobenzothiophenes C from easily accessible phenylthioacetamides A, through a 6π-electrocyclization involving a keteniminium [31 -35] salt intermediate B, we were eager to extend this approach towards the formation of 3-aminothiophenes E (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%